Raising Awareness of Sexual Abuse among Children with Intellectual Disabilities: A Survey of Teachers’ Views - Abuzaid, Suad M.O. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Sexual abuse is one of the most dangerous phenomena that can overwhelm any society. Children with ID seem to be among the groups with the highest risks for sexual abuse/maltreatment. This research aims to investigate teachers’ views regarding how raising awareness of sexual abuse among children with intellectual disabilities. This phenomenon is not spared even the mentally handicapped, as they may not realize the extent of the abuse they are exposed to and may not tell anyone about it, because they do not understand it, they may not realize the standards of religion, society, and standards of social behavior. The sample was 40 teachers of children with intellectual disabilities from Madina El Monawara. This study utilized a qualitative research technique. To collect data, a semi-structured interview method was employed. In response to some big questions: What causes for high prevalence rates of sexual abuse in individuals with ID? How to raise children with intellectual disabilities’ awareness of Sexual Abuse? According to teachers’ views, lack of social skills, lack of sexual knowledge, inequality in relationships, and the fact that in some cases, individuals with ID need to depend on others were the main causes. Educating children with ID to say no to bad touches, getting to report being victims of sexual abuse, getting them to understand what sexual abuse is or that sexual abuse is a crime, not to be afraid of repercussions they may face from their abuser, or feel ashamed, embarrassed, or blame themselves for the abuse are the most frequently reported recommendations to raise children with intellectual disabilities’ awareness of Sexual Abuse.